What Goes Wrong in Winter? An analysis of the possible causes of the increased bed pressures in acute hospitals in the winter months. - Walmsley, P P (2012)
It is well understood in healthcare circles that winter sees increased pressures on hospital services. What is not as well understood is the cause of these pressures. Using a literature review to develop a series of issues which were then used to focus the interviews of key players involved in managing winter, this project intended to increase understanding of the causes of increased winter pressures. Key themes that came to light included increased acuity of patients, the impact of New Public Management, variability in practice, slow discharge processes and failure to correct internal processes in the hospital. The analysis highlighted a strong blame culture and a disjointed approach to care of patients. These issues were exacerbated by targets allocated to sections of the pathway. Better integration of services and development of targets that apply to the whole patient pathway would improve the patient experience. Further work needs to be done regarding integrating services to have a common purpose around patient outcomes. The study shows the need for an integrated, whole pathway approach with a shared purpose across the healthcare team.